In‐hospital and 90‐day outcomes after total pancreatectomy with islet autotransplantation for pediatric chronic and acute recurrent pancreatitis. Issue 4 (6th December 2018) - Kotagal, Meera; Slusher, Joyce; Ahmad, Syed; Aronson, Lori A.; Brunner, John; Chima, Ranjit; Elder, Deborah A.; Goldschneider, Kenneth R.; Hornung, Lindsey; Lin, Tom K.; Ogg, Stephen M.; Palermo, Joseph J.; et al.
Abstract : Total pancreatectomy with islet autotransplantation (TPIAT) is used to treat debilitating chronic pancreatitis (CP) and acute recurrent pancreatitis (ARP) that has failed medical and endoscopic therapy. We performed a retrospective review of TPIAT patients at a free‐standing children's hospital to evaluate perioperative outcomes. Twenty patients (median age 13, 65% female) underwent TPIAT (2015 through 2017). Of the 20 patients, 95% had CP and 1 patient (5%) had ARP alone. Seventy‐five percent of the patients had a pancreatitis‐associated genetic mutation; 40% had pancreas divisum. The median surgical time was 757 (IQR 657 to 835) minutes. Median islet equivalents per kg of body weight (IEQ/kg) were 6404 (IQR 5018 to 7554). At 90 days postoperatively vs preoperatively, significantly fewer patients were receiving parenteral nutrition (0% vs 25%, P = .006) and opioids (45% vs 75%, P = .01). Short Form 36‐Item Health Survey (SF‐36) physical health module scores and total scores improved (34.0 preoperatively vs 54.6 at 90 days, P = .008, and 47.1 vs 65.3, P = .007, respectively); SF‐10 physical health scores also improved (13.4 vs 33.1, P = .02). Insulin requirement decreased from 0.5 unit/kg/day to 0.4 unit/kg/day between discharge and 90 days ( P = .02). TPIAT is an effective option when debilitating disease persists despite maximal medical and endoscopic therapy. Opioid, parenteral nutrition, and exogenous insulin use can successfully be weaned within 90 days after TPIAT, with gains in health‐related quality of life. Abstract : A retrospective review of 20 pediatric patients undergoing total pancreatectomy with islet autotransplantation demonstrates that this is an effective treatment option for pediatric acute recurrent and chronic pancreatitis, allowing patients to be weaned from opioid, parenteral nutrition, and exogenous insulin use within 90 days posttransplant with significant gains in health‐related quality of life.